Spiritualisme: Problem Sosial dan Keagamaan Kita - Roibin Roibin (el Harakah: Jurnal Budaya Islam, 2002)
In principle, the original spiritual movement is more a sociological symptom and leads to the religious. It happens not because of the great currents of foreign culture, but rather as a result of the daily routine of our lives that is rapidly changing from day to day. The very basic function of avoiding this negative attitude is perhaps to put forward the feeling and reasoning that in our own socio-politics and culture, it is not uncommon to give rise to the various social tensions that constitute the embryo of the emergence of spiritualism. And then who has the authority to judge about the phenomena of spiritualism, either the first or the second? Is there any religion in this phenomenon? The phenomenon of spirituality is essentially social in nature, but then why is spiritualism more individualistic, and ignorant of the problems of others? This is where the basic standard, which then used as a tool to measure the extent of the validity of the phenomenon of spiritualism. Pada prinsipnya gerakan spiritualisme semula lebih merupakan gejala sosiologis dan bermuara ke arah agamis. Ia terjadi bukan karena arus besar kebudayaan asing, melainkan sebagai akibat dari corak rutinitas keseharian hidup kita yang cepat berubah dari hari ke hari. Fungsi yang sangat mendasar dari upaya menghindari sikap negatif ini adalah mungkin untuk lebih mengedepankan perasaan dan penalaran bahwa di dalam sosial-politik dan kebudayaan yang kita disain sendiri, tidak jarang telah melahirkan berbagai ketegangan-ketegangan sosial yang merupakan embrio munculnya spiritualisme. Dan selanjutnya siapa yang memiliki otoritas penilaian tentang gejala spiritualisme tersebut, baik model yang pertama ataupun yang kedua? Adakah andil agama dalam fenomena ini? Gejala spiritualitas itu pada hakekatnya pro sosial sifatnya, tetapi kemudian mengapa spiritualisme lebih cenderung individualistik, dan abai pada persoalan-persoalan orang lain? Disinilah standar  mendasarnya , yang kemudian dijadikan alat untuk mengukur sejauh mana keabsahan fenomena spiritualisme tersebut.